Comparision of doxorubicin-induced cardiotoxicity in the ICR mice of different sources - Kim, Sou Hyun; Kim, Keuk-Jun; Kim, Joung-Hee; Kwak, Jae-Hwan; Song, HyunKeun; Cho, Joon Young; Hwang, Dae Youn; Kim, Kil Soo; Jung, Young-Suk (Laboratory animal research, 2017)
Doxorubicin is a widely used chemotherapeutic agents and is now part of standard therapeutic regimens for a variety of cancers (eg, hematopoietic malignancies and advanced solid tumors of the breast, ovary, thyroid, and bone). However, a potentially lethal and dose-dependent cardiotoxicity that appears within a short time after treatment limits the usage of doxorubicin in cancer patients. Although the mechanism of doxorubicin-induced cardiotoxicity is not completely understood, it is thought that free radical-induced oxidative stress and excessive production of reactive oxygen species are primary drivers of its toxicity. In this study, we compared the doxorubicin-induced cardiotoxicity of ICR mice obtained from three different sources and evaluated the utility of Korl:ICR stock established by the Korean FDA. Because doxorubicin-induced cardiotoxicity is thought to involve the excessive generation of ROS followed by oxidative stress, we determined the representative tissue index of oxidation, lipid peroxidation, and antioxidant, glutathione (GSH), as well as the parameters of heart injury. Doxorubicin treatment successfully induced cardiotoxicity as evidenced by histological examination and serum parameters (eg, levels of LDH and CK activities) in ICR mice. It was accompanied by increased lipid peroxidation and a decrease in both cysteine and GSH, further supporting previous reports that oxidative stress is a potential mechanism of doxorubicin-induced cardiotoxicity. Of interest, we did not observe a significant difference in doxorubicin-induced cardiotoxicity among mice of different origins. Collectively, our results suggest that Korl:ICR strain may be useful in the research of doxorubicin-induced cardiotoxicity.